MENINGKATKAN KOMPETENSI SISWA MEMAHAMI RANGKAIAN LISTRIK SEDERHANA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE GRUP INVESTIGASI DI KELAS IX-J SMPN 1 SIDIKALANG - Manahan Marianus Anggiat Simbolon (Universitas Negeri Medan, 2018)
Abstract : Improving Student Competency Understanding Simple Electric Circuits Through Cooperative Learning Model Type of Investigation Group in Class IX-J SMPN 1 Sidikalang. This study aims to improve students' learning activity by applying the Group Investigative Group (GI) learning model during teaching and learning activities and improve student learning outcomes. This type of research is classroom action research (PTK) using two cycles. Subjects in this study were students of class IX-J SMP Negeri 1 Sidikalang with the number of students as much as 36 people. The results of research after the implementation of cooperative learning model type Investigation Group is: Mastery of students' competence in the material range of simple electrical output increased from cycle I to cycle II is marked by the increase of student learning outcomes.Keywords: Cooperative Learning Model Type Group Investigation, Learning Activity, Learning Outcomes.Abstrak : Meningkatkan Kompetensi Siswa Memahami Rangkaian Listrik Sederhana Melalui Model Pembelajaran Kooperatif Tipe Grup Investigasi di Kelas IX-J SMPN 1 Sidikalang. Penelitian ini bertujuan untuk meningkatkan keaktifan belajar siswa dengan diterapkannya model pembelajarankooperatif tipe Grup Investigasi (GI) selama kegiatan belajar mengajar dan meningkatkan hasil belajar siswa. Jenis peneltian ini adalah penelitian tindakan kelas (PTK) dengan menggunakan dua siklus. Subjek dalam penelitian ini adalah siswa kelas IX-J SMP Negeri 1 Sidikalang dengan jumlah siswa sebanyak 36 orang. Adapun hasil penelitian setelah diterapkannnya model pembelajaran kooperatif tipe Grup Investigasi adalah: Penguasaan kompetensi siswa pada materi rangakaian listrik sederhana meningkat dari siklus I ke siklus II ditandai dengan meningkatnya hasil belajar siswa.Kata Kunci : Model Pembelajaran Kooperatif Tipe Grup Investigasi, Aktivitas Belajar, Hasil Belajar.